Ensino de inglês para fins específicos: um estudo sobre os recursos tecnológicos e metodológicos do curso esp-t para profissionais da saúde - Lacerda, Jacqueline Rose Di (2016)
This research has had as a general goal to analyze the esp-t course from the online Erasmus platform which is addressed to health professionals. The technological and methodological aspects have been investigated through a comparative analysis of the ICT resources and methodology used in this course along with the criteria listed in the reference frameworks of Doughty and Long (2003) and Basturkmen (2006, 2010). This is a qualitative research, evaluative in type, with descriptive exploratory objective. Our research was based on a literature review on teaching ESP for health professionals in the digital context. The esp-t course was selected because it is a free ESP course, available online with open access to therapists and to health professionals aiming at language improvement for certification purposes. The researcher has enrolled herself in this course so she could live the experience of studying IFE in an open virtual platform and could develop a reflective diary, composed of personal notes and screenshots of the course attended. The data were analyzed based on reference frameworks and the results have shown that although the platform has the potential for the use of interactive activities, there is a predominance of exercises aiming at the development of reading and listening comprehension language skills.